Labile and recalcitrant fractions of soil organic matter under integrated crop‑livestock system - da Silva, Eulene Francisco; Lourente, Elaine Pinheiro Reis; Marchetti, Marlene Estevão; Mercante, Fábio Martins; Ferreira, Ana Karolina Teixeira; Fujii, Gisele Carneiro (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the soil total organic carbon (TOC) and total nitrogen (TN) stocks, C and N in labile and recalcitrant fractions of the soil organic matter (SOM), and the C management index, in soils under integrated crop-livestock (ICL) system after four (ICL4) and eight years (ICL8) of settlement. For comparison purposes, other management systems were used: pasture and crop under no tillage (NT), besides native vegetation. The experiment was carried out in a completely randomized block design, with five replicates. The crop-livestock established in a period of eight years can reach a new steady state equivalent to the no-tillage with 23 years of implementation. There was accumulation in total organic carbon of 101.0 (ICL8) and 104.2 Mg ha-1 (NT), and N total stock of 5.5 (ICL8) and 5.8 Mg ha-1 (NT) in the 0–30 cm layer, as well as increase in the stock of labile and recalcitrant C and N fractions of SOM. For crop-livestock with eight years, the C management index of 88 was higher than other management systems, and not different from native vegetation (0–10 cm), however, it was similar to NT in the analysis of the entire profile (0–30 cm).